Teaching work in COVID-19 times: between written and lived in remote teaching - Cavalcante, Petronio; Ozorio, Francisca Janaina Dantas Galvao; Gomes, Roberia Vieira Barreto; Muniz, Querem Hapuque Monteiro Alves; Paim, Igor de Moraes [UNESP] (Fundacao Univ Tocantins, 2022)
The objective of this study is to analyze how basic education teachers in the city of Fortaleza/CE develop their teaching work in times of social distancing, due to Covid-19. Therefore, we opted for a qualitative approach, of an exploratory nature, of case study type, bibliographic and documentary, to analyze the work and teaching knowledge, the conceptions about Covid-19 and the SME/Fortaleza guidelines for remote work due to the consequences of the pandemic. As a strategy to approach the subjects, six teachers from different segments working in public schools in Fortaleza/CE were asked to describe, through the writing of a Pedagogical Letter', how their work is being developed during this period. The results showed that, even under multiple pressure and challenges, teachers have always been imbued with genuine effort and a sense of superior ethical purpose to deal with the confrontations of remote teaching. In addition, we noticed the discomfort of not being able to equip and empower their students as they deserve, however, amid all the emotional and even physical exhaustion, these teachers do not tire of betting on the development of their students, never leaving aside the reception and affection in their pedagogical actions.
Keywords: Teaching Work; Teaching knowledge; Covid-19; Remote Teaching